Tax Payment Intention using Theory of Planned Behavior Approach - Much. Riyadus Solichin; Susi Astuti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Taxes are the most reliable source of the State Revenue and Expenditure Budget (APBN). Without taxes, the Indonesian government may not be able to develop all the infrastructure from the life sector of the state and human resource development that cannot meet the requirements. The purpose of this study is to test and prove empirically based on and payment of taxes using the Theory of Planned Behavior approach, this research also add tax sanction as determinant of intention. The population of this study is the Corporate Taxpayers in Kebumen Regency. The sample used in this research is the owner of hotels and restaurants in Kebumen Regency as many as 54 respondents. The hypothesis in this study was tested using SEM with WarpPLS 7.0 software. The results of the hypothesis found that theory of planned behavior can explain the intention of hotel and restaurant taxpayers in paying taxes. In addition, it is also found that tax sanctions have a positive effect on intention